Bloomsbury Open Collections: A new model for open access monographs - Bruce, Charlotte; Iwanikiw, Lianna; Pyne, Ros (Septentrio Conference Series, 2023)
Open access brings important benefits to scholarly books and their authors. Research shows open access publication can substantially increase and diversify monograph readership, supporting and amplifying a worldwide interest in scholarship in the arts, humanities, and social sciences. But, while open access provides greater equality for readers, the prevailing fee-based models exclude many authors. To address this challenge, Bloomsbury has this year launched a new model, Bloomsbury Open Collections, that aims to offer open access for books in a way that is sustainable for us as a publisher, but which does not rely on fees paid by individual authors’ institutions and funders. Through this model, we are aiming to make open access publication available to a wider range of scholarly book authors by spreading the cost across multiple organisations, while providing additional benefits to participating libraries. Our hope is to engage a more diverse set of authors, bringing their work to a wider global audience. In this poster we share details of how our open access monographs pilot works in practice and how we went about developing the model. We provide insights into how feedback from librarians shaped our approach, and how we have sought to incorporate transparency into the model. We also discuss the principles we used to select titles for inclusion in the pilot, and share some early feedback from our author community.